Criteria for Structural Differentiation of Innovation Industries in the System of Creative Industries - Borisova, Vladya (Research Papers, 2017)
The study examines the structuring of innovation industries in the system of creative industries, introducing into the problem by clarifying the specifics of the knowledge economy and the typical for it new economic resources such as knowledge and creativity. It emphasizes the importance of intellectual property for the formation of the fourth economic sector, the so-called creative sector, and for its relation with the traditional three-sector model. The study identifies the creative industries through intellectual property as a classification criterion, and defines the innovation ones as leading in shaping economic indicators such as employment, added value and GDP. The study outlines the essence and the structural units of innovative industries, the specifics of their activities as business participants along the value chain. It analyzes the characteristics and the process of creating, producing and marketing the innovation product by defining the stages and specific activities of each one of them. In addition, the study brings out classification criteria for the types of innovation products. The innovation industries’ market has been identified and its main features and specifics are brought out.
Keywords: Intellectual property; Knowledge economy; Creative sector; Creative industries; Innovation industry; Product; Market